Bacterial type III secretion systems: a complex device for the delivery of bacterial effector proteins into eukaryotic host cells. Issue 19 (9th August 2018) - Wagner, Samuel; Grin, Iwan; Malmsheimer, Silke; Singh, Nidhi; Torres-Vargas, Claudia E; Westerhausen, Sibel
Abstract: Virulence-associated type III secretion systems (T3SS) serve the injection of bacterial effector proteins into eukaryotic host cells. They are able to secrete a great diversity of substrate proteins in order to modulate host cell function, and have evolved to sense host cell contact and to inject their substrates through a translocon pore in the host cell membrane. T3SS substrates contain an N-terminal signal sequence and often a chaperone-binding domain for cognate T3SS chaperones. These signals guide the substrates to the machine where substrates are unfolded and handed over to the secretion channel formed by the transmembrane domains of the export apparatus components and by the needle filament. Secretion itself is driven by the proton motive force across the bacterial inner membrane. The needle filament measures 20–150 nm in length and is crowned by a needle tip that mediates host-cell sensing. Secretion through T3SS is a highly regulated process with early, intermediate and late substrates. A strict secretion hierarchy is required to build an injectisome capable of reaching, sensing and penetrating the host cell membrane, before host cell-acting effector proteins are deployed. Here, we review the recent progress on elucidating the assembly, structure and function of T3SS injectisomes. Abstract : Type III secretion systems: complex devices for the delivery of bacterial effector proteins into eukaryotic host cells.